1991
DOI: 10.1016/0161-7346(91)90074-r
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of lesion detection by echographic image processing: Signal-to-noise-ratio imaging

Abstract: Signal-to-noise-ratio (SNR) images were constructed by a sliding window technique. Theoretical derivations of the first order statistical properties of SNR images are given for the case of intensity coding of the original images for low number densities and for the limit case of fully developed speckle. The original images were obtained by realistic simulations of backscattering by homogeneous media, while using a range of number densities of the scatterers (isotropic scattering). The SNR imaging method is ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Although the approximation looks rather poor, it does produce good predictions. For example, the SD of the average value is predicted by (20) and can use either (10) or the approximation (13). With the in vivo parameters, it can be shown that the two predicted SDs are nearly identical in the window size range used in this study.…”
Section: B Correlation Coefficient Including Ipbmentioning
confidence: 84%
See 2 more Smart Citations
“…Although the approximation looks rather poor, it does produce good predictions. For example, the SD of the average value is predicted by (20) and can use either (10) or the approximation (13). With the in vivo parameters, it can be shown that the two predicted SDs are nearly identical in the window size range used in this study.…”
Section: B Correlation Coefficient Including Ipbmentioning
confidence: 84%
“…Even without IPB there already is a window size dependence, because in windows in the order of the speckle size the correlation between pixels tends to underestimate s w , which results in an increased SNR. This relation is well known [20], [21]. The relation between window size and expected SNR in the presence of IPB is derived in the Appendix.…”
Section: A the Accuracy Of The Snrmentioning
confidence: 90%
See 1 more Smart Citation
“…Adaptive filtering might be based on the original B-mode gray level images, but various other gray level encodings have also been tried. Local first-order and second-order statistical parameters that were used are: mean (Bamber and Daft 1986), median (Loupas et al 1989), signal-to-noise ratio (inverse of the coefficient of variation; Verhoeven et al (1991), root-mean-squares (Kotropoulos and Pitas 1992) and mean squares (this paper). For a general assessment of adaptive filtering see Verhoeven and Thijssen (1993).…”
Section: Introductionmentioning
confidence: 99%
“…Local first order and second order statistical parameters that were used are: mean 14 , median 15 , signal-tonoise ratio (inverse of coefficient of variation 16 ), root-mean-squares 17 , mean squares (this paper). See for a general assessment of adaptive filtering.…”
Section: Introductionmentioning
confidence: 99%